Amphibian regeneration and mammalian cancer: Similarities and contrasts from an evolutionary biology perspective: Comparing the regenerative potential of mammalian embryos and urodeles to develop effective strategies against human cancer. (10th March 2021) - Corradetti, Bruna; Dogra, Prashant; Pisano, Simone; Wang, Zhihui; Ferrari, Mauro; Chen, Shu‐hsia; Sidman, Richard L.; Pasqualini, Renata; Arap, Wadih; Cristini, Vittorio
Abstract: Here we review and discuss the link between regeneration capacity and tumor suppression comparing mammals (embryos versus adults) with highly regenerative vertebrates. Similar to mammal embryo morphogenesis, in amphibians (essentially newts and salamanders) the reparative process relies on a precise molecular and cellular machinery capable of sensing abnormal signals and actively reprograming or eliminating them. As the embryo's evil twin, tumor also retains common functional attributes. The immune system plays a pivotal role in maintaining a physiological balance to provide surveillance against tumor initiation or to support its initiation and progression. We speculate that susceptibility to cancer development in adult mammals may be determined by the loss of an advanced regenerative capability during evolution and believe that gaining mechanistic insights into how regenerative capacity linked to tumor suppression is postnatally lost in mammals might illuminate an as yet unrecognized route to cancer treatment. Abstract : Regeneration, morphogenesis and cancer. This manuscript provides an evolutionary perspective on the regenerative potential of mammals and amphibians as means to yield effective regenerative medicine‐based strategies to prevent and fight human cancer.